COVID-19: Analysis of Factors Affecting the Economy of Hunan Province Based on the Spatial Econometric Model - Pan, Wen-Tsao; Zhonghuan, Wu; Shiqi, Chen; Siyi, Xiao; Yanping, Tang; Danying, Liang (Frontiers in Public Health, 2022)
The COVID-19 pandemic spread across the country, and it has a negative impact on Hunan province, especially the economic downturn. In this paper, we take 14 prefecture-level cities in Hunan to find influencing factors and effects on economic downturn based on the spatial econometric model. And the data of 2019 were conducted in geoda software to get Molain Index (Moran’s I). To deeply analyze the impact of each factor on the economy, the panel data from 2015 to 2019 were conducted in MATLAB. The results show that the spatial correlation of the cities around chang-zhu-tan is high, and the economic growth of whole province can be influenced by these cities. They should do more to restore the economy, such as reduce the tax revenue, improve the local financial revenue, reduce the ineffective educational input and so on.